Randomized, controlled trial of entecavir versus placebo in children with hepatitis B envelope antigen–positive chronic hepatitis B. Issue 2 (16th October 2015) - Jonas, Maureen M.; Chang, Mei‐Hwei; Sokal, Etienne; Schwarz, Kathleen B.; Kelly, Deirdre; Kim, Kyung Mo; Ling, Simon C.; Rosenthal, Philip; Oraseanu, Dumitru; Reynolds, Laurie; Thiry, Alexandra; Ackerman, Peter
Abstract : This ongoing, randomized phase III study assesses the safety and efficacy of entecavir versus placebo in nucleos(t)ide‐naïve children (2 to <18 years) with hepatitis B envelope antigen (HBeAg)‐positive chronic hepatitis B (CHB). Blinded treatment was administered for a minimum of 48 weeks. After week 48, patients with HBeAg seroconversion continued blinded treatment; those without switched to open‐label entecavir. The primary endpoint was HBeAg seroconversion and HBV DNA <50 IU/mL at week 48. A total of 180 patients were randomized (2:1) and treated. Baseline median age was 12 years, with approximately 50% of children ages >12 to <18, and 25% each ages ≥2 to ≤6 and >6 to ≤12. Rates for the primary endpoint at week 48 were significantly higher with entecavir than placebo (24.2% [29 of 120] vs. 3.3% [2 of 60]; P  = 0.0008). Furthermore, higher response rates were observed with entecavir compared with placebo for the key week 48 secondary endpoints: HBV DNA <50 IU/mL (49.2% [59 of 120] vs. 3.3% [2 of 60]; P  < 0.0001); alanine aminotransferase normalization (67.5% [81 of 120] vs. 23.3% [14 of 60]; P  < 0.0001); and HBeAg seroconversion (24.2% [29 of 120] vs. 10.0% [6 of 60]; P  = 0.0210). Among entecavir‐randomized patients, there was an increase in all efficacy endpoints between weeks 48 and 96, including an increase from 49% to 64% in virological suppression. The cumulative probability of emergent entecavir resistance through years 1 and 2 of entecavir was 0.6% and 2.6%, respectively. Entecavir was well tolerated with no observed differences in adverse events or changes in growth compared with placebo. Conclusion : In childhood CHB, entecavir demonstrated superior antiviral efficacy to placebo with a favorable safety profile. These results support the use of entecavir as a therapeutic option in children and adolescents with CHB. (Hepatology 2016;63:377–387)